2014
DOI: 10.1371/journal.pone.0102912
|View full text |Cite
|
Sign up to set email alerts
|

Using Participatory Risk Mapping (PRM) to Identify and Understand People's Perceptions of Crop Loss to Animals in Uganda

Abstract: Considering how people perceive risks to their livelihoods from local wildlife is central to (i) understanding the impact of crop damage by animals on local people and (ii) recognising how this influences their interactions with, and attitudes towards, wildlife. Participatory risk mapping (PRM) is a simple, analytical tool that can be used to identify and classify risk within communities. Here we use it to explore local people's perceptions of crop damage by wildlife and the animal species involved. Interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…Our results concur with research near Tarangire National Park in Tanzania, where human disease, drought, and conservation were identified as risks, and respondents were particularly concerned that conservation policies might limit land use or confiscate land for park expansion (Baird et al 2009). Quinn et al (2003) found disease and water availability to be two of the most important risks in semi-arid villages in central and northeast Tanzania, while Webber and Hill (2014) found high crop-raiding severity in communities near Budongo Forest Reserve, adjacent to MFNP.…”
Section: Discussionmentioning
confidence: 99%
“…Our results concur with research near Tarangire National Park in Tanzania, where human disease, drought, and conservation were identified as risks, and respondents were particularly concerned that conservation policies might limit land use or confiscate land for park expansion (Baird et al 2009). Quinn et al (2003) found disease and water availability to be two of the most important risks in semi-arid villages in central and northeast Tanzania, while Webber and Hill (2014) found high crop-raiding severity in communities near Budongo Forest Reserve, adjacent to MFNP.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that simply quantifying losses does not account for the complicated relationships that people hold towards perceived risk factors (Webber & Hill, 2014). The validity of the conclusions in this research should therefore not be affected by the lack of ground-truthing -although there is still value in understanding the difference between perception and reality of wildlife damage (Webber & Hill, 2014).…”
Section: Limitationsmentioning
confidence: 88%
“…worker job satisfaction or worker salary) in common throughout depredation hotspots, it is often perceived damage that is the strongest driver of attitudes and behaviour rather than the real loss (Marker et al, 2003;Mishra, 1997). This indicates that simply quantifying losses does not account for the complicated relationships that people hold towards perceived risk factors (Webber & Hill, 2014). The validity of the conclusions in this research should therefore not be affected by the lack of ground-truthing -although there is still value in understanding the difference between perception and reality of wildlife damage (Webber & Hill, 2014).…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, the different orders were clustered as first, second, and third order vulnerabilities of climate change impacts. The authors also used risk and resource mapping (RRM) to collect information on land, water, crops and other local resources (resource mapping) and on climatic risks on significant local resources (risk mapping) [70,72]. RRM was carried out with the same group of participants.…”
Section: Methodsmentioning
confidence: 99%